Interactions between Plasma Membrane Aquaporins Modulate Their Water Channel Activity - Fetter, Karolina (American Society of Plant Biologists, 2004)
Plant plasma membrane intrinsic proteins (PIPs) cluster in two evolutionary subgroups, PIP1 and PIP2, with different aquaporin activities when expressed in Xenopus oocytes. Maize ZmPIP1;1 and ZmPIP1;2 do not increase the osmotic water permeability coefficient (P(f)), whereas ZmPIP2;1, ZmPIP2;4, and ZmPIP2;5 do. Here, we show that coexpression of the nonfunctional ZmPIP1;2 and the functional ZmPIP2;1, ZmPIP2;4, or ZmPIP2;5 resulted in an increase in P(f) that was dependent on the amount of injected ZmPIP1;2 complementary RNA. Confocal analysis of oocytes expressing ZmPIP1;2–green fluorescent protein (GFP) alone or ZmPIP1;2-GFP plus ZmPIP2;5 showed that the amount of ZmPIP1;2-GFP present in the plasma membrane was significantly greater in coexpressing cells. Nickel affinity chromatography purification of ZmPIP2;1 fused to a His tag coeluted with ZmPIP1;2-GFP demonstrated physical interaction and heteromerization of both isoforms. Interestingly, coexpression of ZmPIP1;1 and ZmPIP2;5 did not result in a greater increase in P(f) than did the expression of ZmPIP2;5 alone, but coexpression of the ZmPIP1;1 and ZmPIP1;2 isoforms induced a P(f) increase, indicating that PIP1 isoform heteromerization is required for both of them to act as functional water channels. Mutational analysis demonstrated the important role of the C-terminal part of loop E in PIP interaction and water channel activity induction. This study has revealed a new mechanism of plant aquaporin regulation that might be important in plant water relations.